Knowledge, Attitude and Practice of Oral Hygiene Among Pupils in Ahenema Kokoben - Opoku, Oscar Agyemang; Yeboah, Erica; Henry, Okudzeto; Plange, Nancy; Nyarko, Juliana (Devotion : Journal of Research and Community Service, 2023)
The study examined the knowledge, attitudes and practices of oral hygiene among students in Ahenema Kokoben. The study employed descriptive design of the quantitative approach. The study sampled 60 respondents of which 85 was made up of students. The study employed questionnaire. With the quantitative data, it was analysed using frequencies and percentages with the aid of Statistical Package for Service Solution. The study found that students were knowledgeable about oral hygiene. Students have good attitude towards oral hygiene. They thought that brushing their teeth regularly will help prevent oral problems; regular visit to dentist is relevant; and think that maintaining good healthy teeth is an individual responsibility. Students have good practice regarding oral hygiene. Respondents spend small time in brushing their teeth while small respondents brush under the supervision of their parents. It was recommended that students should be encouraged to continue to visit the dentist regularly and not to wait till they have issue with their teeth. Also, students should be encouraged to spend more time in brushing their teeth regularly and also twice a day. Moreover, parents should be encouraged to supervise their children when brushing their teeth, especially, among students who have decayed teeth or oral problems. Students should be educated or sensitize about the negative effect of sweet on their oral health. Rinsing of their mouth after meals should be encouraged among students to ensure proper oral hygiene.